Understanding Saudi EFL teachers' technology integration experiences in university English instruction - Fadi Maher Al-Khasawneh; Sahar Mohammed Alshawaf (Journal on English as a Foreign Language, 2026)
Digital tools are increasingly available in higher education, yet meaningful integration depends on educators' acceptance and professional competencies. EFL teachers' lived experiences with technology integration remain underexplored in the literature. This case study investigates how Saudi EFL teachers integrate technology in English language teaching. Twelve EFL teachers at a Saudi university were purposively selected as participants. Data were collected through semi-structured interviews and were analyzed thematically. Results reveal that teachers used technology strategically to strengthen relationships and enhance traditional instruction, treating it as an engagement tool rather than a driver of fundamental pedagogical change. Their positive attitudes were constrained by interconnected barriers, including limited institutional access, inadequate training, and concerns about relevance and student capability. Technology integration thus emerges as a balancing act between teaching goals and real-world limitations. These findings suggest that effective technology integration requires holistic institutional support addressing both infrastructure and human development. Policymakers and academic leaders should prioritize targeted professional development programs and context-sensitive support systems to better equip EFL teachers in similar settings.